Social infrastructures in research communication: A personal view of the FORCE11 story - Neylon, Cameron (2018)
There are a wide range of community organizations and projects that aim to support scholarly communications in one way or another. Scholarly societies are some of the longest standing and, as research communication has changed, new groups, organizations and projects appear – to solve problems and fill gaps. Amongst these organizations, FORCE11 has acted as a nucleus, support platform and convening point for community efforts on issues as wide-ranging as identifiers for research materials, implementing data and software citation systems, and on what we might mean when we talk about building a ‘scholarly commons’. I have personally been involved in FORCE11, attending the meetings that led to its formation, as a founding board member of the formal organization and, most recently, serving as President of the Board up until the end of 2017. In this article I give an entirely personal view, drawing on my perspective of those experiences and what it can do to illuminate the roles and interactions of the many organizations seeking to support change in research communications.